2022
DOI: 10.3390/ma15041498
|View full text |Cite
|
Sign up to set email alerts
|

Long Spiky Au-Ag Nanostar Based Fiber Probe for Surface Enhanced Raman Spectroscopy

Abstract: The detection performances of noble metal-based surface enhanced Raman spectroscopy (SERS) devices are determined by the compositions and geometries of the metal nanostructures, as well as the substrates. In the current study, long spiky Au-Ag alloy nanostars were synthesized, and both core diameters and spike lengths were controlled by Lauryl sulfobetaine concentrations (as the nanostructure growth skeleton). The long spiky star geometries were confirmed by transmission electron micrograph images. Elements en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…He et al synthesized long, spiky Au–Ag alloy nanostars using one‐pot seedless green synthetic method and explored their potential as a surface enhanced Raman spectroscopy probe. Figure 8 shows the TEM of these Au–Ag nanostars along with their optical properties in NIR (He et al, 2022). Biosynthesis of nanostars using a strain of Saccaropolyspora hirsute has also been investigated by Eslam et al In this report, the biosynthesized silver nanostars demonstrated antimicrobial characteristics using agar diffusion method against various pathogens such as Staphylococcus aureus ( S. aureus ), Candida albicans , and Streptococcus pyogenes (Sholkamy et al, 2019).…”
Section: Shape‐controlled Synthesis and Properties Of Metallic Nanopa...mentioning
confidence: 99%
See 1 more Smart Citation
“…He et al synthesized long, spiky Au–Ag alloy nanostars using one‐pot seedless green synthetic method and explored their potential as a surface enhanced Raman spectroscopy probe. Figure 8 shows the TEM of these Au–Ag nanostars along with their optical properties in NIR (He et al, 2022). Biosynthesis of nanostars using a strain of Saccaropolyspora hirsute has also been investigated by Eslam et al In this report, the biosynthesized silver nanostars demonstrated antimicrobial characteristics using agar diffusion method against various pathogens such as Staphylococcus aureus ( S. aureus ), Candida albicans , and Streptococcus pyogenes (Sholkamy et al, 2019).…”
Section: Shape‐controlled Synthesis and Properties Of Metallic Nanopa...mentioning
confidence: 99%
“…Insert images represents singular nanostar morphology, and (e) extinction spectra of the nanostructures. Figure reproduced with permission from reference He et al (2022).…”
Section: Shape‐controlled Synthesis and Properties Of Metallic Nanopa...mentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) technology has been widely used in the detection of trace amounts of substances in recent decades due to its competitive merits such as high sensitivity and rapid detection of low concentration analytes, high specificity due to rich vibration fingerprint information with narrow Raman peaks, and simplicity and practicability with portable instrument [24][25][26]. For the better application of SERS technique, an important requirement is to fabricate highly stable, reliable, and reproducible metallic nanostructures substrates, which can generate intensively localized electromagnetic fields at gaps between plasmonic nanostructures [27][28][29].…”
Section: Introductionmentioning
confidence: 99%